Empathy and burnout: a study on residents from a Singapore institution - Lee, Phong Teck (Singapore Med J, 2018)
INTRODUCTION: Empathy and burnout are two entities that are important in a physician’s career. They are likely to relate to each other and can be heavily influenced by surrounding factors, such as medical education, local practices and cultural expectations. To our knowledge, empathy and burnout studies have not been performed in Singapore. This study was designed to evaluate empathy and burnout levels using the Jefferson Scale of Physician Empathy (JSPE) and Maslach Burnout Inventory (MBI) among residents in Singapore, and compare them with the United States (US) literature. METHODS: The JSPE, MBI and a self-designed questionnaire were completed by 446 trainees at a residency-sponsoring institution in Singapore. RESULTS: Residents in Singapore had lower empathy and higher rates of burnout compared to US literature. Physician empathy was associated with burnout: residents with higher empathy scores had higher personal accomplishment (p < 0.001, r = 0.477, r(2) = 0.200); and lower emotional exhaustion (p < 0.001, r = 0.187, r(2) = 0.035) and depersonalisation (p < 0.001, r = 0.321, r(2) = 0.103) scores. CONCLUSION: Residents in Singapore had lower empathy and higher burnout scores compared to the US literature. Further research into the underlying cause is imperative to guide intervention.